Preterm preeclampsia screening and prevention: a comprehensive approach to implementation in a real-world setting - Stefania Ronzoni; Shamim Rashid; Aimee Santoro; Elad Mei-Dan; Jon Barrett; Nanette Okun; Tianhua Huang (BMC Pregnancy and Childbirth)
Abstract Background Preeclampsia significantly impacts maternal and perinatal health. Early screening using advanced models and primary prevention with low-dose acetylsalicylic acid for high-risk populations is crucial to reduce the disease’s incidence. This study assesses the feasibility of implementing preterm preeclampsia screening and prevention by leveraging information from our current aneuploidy screening program in a real-world setting with geographic separation clinical site and laboratory analysis site. Methods A prospective cohort study involved pregnant individuals undergoing nuchal translucency scans between 11 and 14 weeks. Risk for preterm preeclampsia was assessed using the Fetal Medicine Foundation algorithm, which includes maternal risk factors, uterine artery Doppler, mean arterial pressure and serum markers (Placental growth factor, PlGF and Pregnancy-associated plasma protein-A, PAPP-A). High-risk patients were offered low-dose acetylsalicylic acid prophylaxis. Feasibility outcomes, such as recruitment rates, protocol adherence, operational impact, integration with existing workflows, screening performance and pregnancy outcomes, were evaluated. Results Out of 974 participants, 15.6% were deemed high-risk for preterm preeclampsia. The study achieved high recruitment (82.1%) and adherence rates, with 95.4% of high-risk patients prescribed low-dose acetylsalicylic acid. Screening performance, adjusted for low-dose acetylsalicylic acid use, showed a detection rate of 88.9–90% (FPR 13.0% and 12.7%) for preterm preeclampsia. High-risk group for preeclampsia had higher incidences of adverse outcomes, including preterm preeclampsia (7.5 vs 0.4%; p < 0.001), preterm delivery (21.2 vs 6.2%; p < 0.001), low birth weight (23.3 vs 5.6%; p < 0.001) and birthweight < 10th percentile (11% vs 5.6%; p = 0.015) compared to low-risk group. The integration of preeclampsia screening had a minimal effect on the time required for aneuploidy screening, with results obtained within a rapid turnaround time. Conclusions The study confirms the feasibility of integrating comprehensive preeclampsia screening into clinical practice, notwithstanding geographic separation between laboratory and clinical settings. It underscores the need for broader adoption and enhanced infrastructure to optimize patient care and outcomes across diverse healthcare settings. Trial registration Clinical trial: NCT04412681 (2020–06-02).